Some Results on The Complete Arcs in Three Dimensional Projective Space Over Galois Field - Al- Mukhtar, A.SH. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The aim of this paper is to introduce the definition of projective 3-space over Galois field GF(q), q = pm, for some prime number p and some integer m.        Also the definitions of (k,n)-arcs, complete arcs, n-secants, the index of the point and the projectively equivalent arcs are given.        Moreover some theorems about these notations are proved.